Síntese direta do acetato de etila a partir do etanol sobre catalisadores de Au, Cu e AuCu suportados em zircônia monoclínica (m-ZrO2) - Lacerda, Camila Raquel de (2018)
The ethanol conversion into ethyl acetate is a very important reaction, in economic and scientific fields. In the context of science, the propose of this work was to evaluate the activity of Au and Cu catalysts supported in m-ZrO2, as well as to evaluate the effect of the addition of different Au contents to the Cu/ZrO2 catalyst. The catalysts were synthesized by the deposition-precipitation method with NaOH and characterized by XRD, N2 physisorption and transmission electron microscopy with chemical mapping of the elements by EDS. The results suggested a high dispersion of the metals on the support without significant changes of the textural properties when adding different metallic contents. Performing catalytic tests in the same conversion basis it was possible to observe that the activity of the catalysts containing Au, both monometallic and bimetallic, is extremely dependent on the Au particle size. The Au monometallic catalysts had an average particle size in the range of 2.2 - 3.1 nm, while the bimetallic ones had a size variation in the 2.5 - 4.1 nm range. Analysis of the apparent rate of formation of the acetaldehyde (AcH) and ethyl acetate (AcOEt) products showed that the addition of Au to the Cu catalyst is beneficial when using a low Au content, resulting in small and well-dispersed particles. However, when the Au content is increased and the particles become larger, the activity of the catalyst to form the product of interest, ethyl acetate, is disadvantageous. The results confirm that Au, when present in small particles, has very favorable electronic properties to the ethanol dehydrogenation to ethyl acetate, both in Au monometallic catalysts and AuCu bimetallic catalysts, proving to be a promising system for this kind of reaction.